Congenital Heterochromia Iridis in a Nigerian Girl Child - Adeosun, B. O. Omolase,M. Y. Majekodunm, Omolase Charles Oluwole, A. K. Akinwaler (Pakistan Journal of Ophthalmology, 2011)
This report is that of a six month old Nigerian girl child with complete heterochromia iridis. There was no associated hypo-pigmentation of her skin or hair. There is no history of similar occurrence in her family. The early presentation of the child may be due to the fact that the parents are enlightened. Cycloplegic refraction done did not reveal any significant refractive error. However we intend to place the patient on coloured contact lens in the nearest future to reduce chromatic aberration to the barest minimum and to conceal the hypo pigmented iris most especially in view of the fact that the patient is a girl child. Though congenital heterochromia iridis appears rare in our population, there is need to educate the general population about this ocular condition so that they can be more receptive to affected individuals.